RESPONSIVITAS PUBLIK: MENGINTEGRASIKAN INDIKASI GEOGRAFIS KOPI DAN MELESTARIKAN KEARIFAN LOKAL OSING DALAM TATA KELOLA BANYUWANGI - Andhika Wahyudiono; Supranoto Supranoto; Edy Wahyudi; Panca Oktawirani; Wheny Khristianto (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
The coffee industry in Banyuwangi requires formal legal safeguards to protect its communal value; nevertheless, the incorporation of Osing local wisdom into Geographic Indications (GI) governance remains routinely overlooked, posing risks to the cultural and economic reputation of coffee producers. This study aims to examine the proactive responsiveness of local government, bureaucratic adaptation mechanisms, and the influence of GI certification on farmer reputation. The methodology outlines a descriptive qualitative approach conducted within primary coffee-producing centres, employing purposeful sampling, interpretative narrative analysis, and data triangulation to ensure research validity. The core theoretical basis comprises communal governance responsiveness, common property regimes, and policy integration models. Findings indicate that local authorities have acted pre-emptively in consolidating technical and cultural datasets into bureaucratic processes; these measures have contributed to a 300–400 per cent rise in coffee production and market value whilst reaffirming Osing customary norms as a central pillar of reputational preservation. The study concludes that GI frameworks have upheld communal ownership principles, strengthened bureaucratic responsiveness, and supported sustainable economic trajectories for farmer communities. Key recommendations propose institutional reinforcement of the MPIG, formalisation of customary standard operating procedures, and market promotion rooted in communal narrative strategies.